ANALYSIS OF ENVIRONMENT-BASED WASTE MANAGEMENT POLICY (CASE STUDY: KALIBOBO URBAN VILLAGE, NABIRE DISTRICT, NABIRE REGENCY) - Isak O. Tebai; Lazarus Ramandei; Rasi Kasim Samosir (International Journal of Multidisciplinary Reseach, 2026)
Waste management remains a critical challenge in developing regions of Eastern Indonesia, particularly in Kalibobo Urban Village, Nabire District, Central Papua Province. This study analyzes the availability of waste management facilities and the implementation of environment-based waste management policy in Kalibobo. A qualitative descriptive approach was employed through field observations, interviews, and secondary data from BPS and the Environmental Agency (DLH) of Nabire Regency. Findings reveal that Kalibobo serves a population of 15,185 residents (3,796 households) with only one waste container far below the SNI 3242:2008 standard requiring 8–19 units. Service coverage is estimated at less than 20% of the village area. The 3R (Reduce, Reuse, Recycle) implementation rate is critically low at approximately 6%, and no TPS3R or waste bank exists. A significant policy-implementation gap is identified between national targets (30% waste reduction, 70% waste handling by 2025) and on-the-ground realities. The study recommends urgent infrastructure expansion, institutionalization of community-based 3R programs, and acceleration of the 2025–2026 DLH Roadmap to achieve sustainable and environment-based waste management.